Reports of the Task Force on Islands, Coral Reefs, Mangroves and Wetlands in Environment and Forests for the Eleventh Five year Plan 2007-2012 - Planning Commission (Planning Commission Government of India, 2007)
"This document synthesizes the findings and recommendations of the Task Force on Islands, Coral Reefs, Mangroves and Wetlands, submitted to the Planning Commission of India for the Eleventh Five Year Plan (2007–2012), along with related national conservation initiatives. It presents a comprehensive assessment of India’s fragile island and coastal ecosystems, with particular emphasis on the Andaman and Nicobar Islands, Lakshadweep Islands, coral reef systems, mangroves, and inland and coastal wetlands. The report highlights the exceptional biodiversity and ecological significance of these ecosystems, alongside their vulnerability to climate change, sea-level rise, coral bleaching, habitat degradation, and increasing anthropogenic pressures. The analysis identifies critical gaps in institutional capacity, enforcement of conservation laws, and integration of local communities into management frameworks. Case studies such as the Gulf of Mannar Marine Biosphere Reserve illustrate the socio-economic tensions between conservation regulations and livelihood dependence, underscoring the need for participatory governance and sustainable alternative livelihoods. The document also reviews national efforts under the National Wetland Conservation Programme, noting substantial progress in wetland identification, Ramsar site designation, management planning, research, and capacity building. Overall, the report advocates an integrated and adaptive approach to ecosystem management, combining strengthened legal frameworks, community participation, scientific monitoring, and sustainable development strategies. Implementing these recommendations is essential to enhance ecosystem resilience, conserve biodiversity, and support the livelihoods of communities dependent on India’s island, coastal, and wetland ecosystems."
Government of India Planning Commission New Delhi (March, 2007)
Keywords: Island Ecosystems; Coral Reefs Conservation; Mangrove Management; Wetland Conservation; Climate Change Impacts; Marine Biodiversity; Andaman and Nicobar Islands; Lakshadweep Islands; Community Participation; Marine Protected Areas; National Wetland Conservation Programme; Sustainable Livelihoods